2015
DOI: 10.4103/0972-124x.164744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral health attitude and behavior among a group of dental students in Puducherry, India: A preliminary cross-sectional study

Abstract: Context:Oral behavior reflects individual perception on oral health. Behavior and attitude of oral health providers, especially dentists, towards oral health affect their capacity to deliver oral health care services. This attitude plays a important role in determining the oral health condition of population.Aim:The purpose of this study is to evaluate the oral health attitude and behavior among a group of dental students in India and to find any gender-based differences in terms of oral health attitude and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
(28 reference statements)
5
15
1
2
Order By: Relevance
“…20 Studies conducted in Lebanon, Thailand, and Malaysia, have also found that female university students have better habits in term of tooth brushing than male students. 21 However, in this study, no significant differences were noted among male and female students.…”
Section: Discussioncontrasting
confidence: 64%
“…20 Studies conducted in Lebanon, Thailand, and Malaysia, have also found that female university students have better habits in term of tooth brushing than male students. 21 However, in this study, no significant differences were noted among male and female students.…”
Section: Discussioncontrasting
confidence: 64%
“…pre-clinical vs basic sciences, and clinical vs pre-clinical or basic sciences) generally had higher HU-DBI scores, representing better oral health attitudes and behavior as students progressed within their academic training, which is in agreement with prior studies. [1920] Students within their clinical year also scored the highest mean within the cognitive effects and previous exposure to dental care constructs when compared to the pre-clinical and basic sciences students. These findings may be attributed not only to increase in the fund of knowledge as students advance through their training but also to their pre-clinical and clinical dental experience, which allows them to apply their knowledge outside the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies evaluated this educational transition in different regions of the world comparing the oral health attitudes and behaviour among preclinical and clinical dental students as primary signs for educational progress. Several outcomes displayed significant improvements of oral health manners in clinical students [4,[10][11][12][13][14][15][16][17], whereas others observed a less effective preclinical-clinical transition [18,19]. Examining the literature, no similar investigation was found in Germany.…”
Section: Introductionmentioning
confidence: 99%